Matrix metalloproteinases – biochemical characteristics and clinical value determination in breast cancer patients - Śliwowska, Izabela; Kopczyński, Zygmunt (Contemporary Oncology/Współczesna Onkologia, 2005)
The matrix metalloproteinases (MMPs) constitute a group of zinc-dependent endopeptidases, which primary function is remodelling of components in the extracellular matrix. These enzymes are synthetized in cells, and secreted to the extracellular space as an inactive form (proMMP). Activation of the enzyme is followed by the cleavage in the propeptide region. The activity of metalloproteinases is strictly regulated at the transcriptional, translation levels and by endogenous inhibitors, including α2-macroglobulin and tissue inhibitors of metalloproteinases (TIMPs). Under physiological conditions matrix metalloproteinases are involved in processes i. e. embryogenesis, angiogenesis, wound healing and in platelet aggregation, regulation of ion metabolism. There is evidence that matrix metalloproteinases activity changes in many pathological conditions, including inflammatory, degenerative disorders and in cancer. Metalloproteinases play an important role in tumor progression by increasing cancer-cell growth, migration, invasion, metastasis and angiogenesis. The expression and activity of MMPs are increased in almost every type of human cancer, and this correlates with tumor stage, increased invasion and potential metastasis, and shortened survival. Among the different MMPs, especially MMP-2 (gelatinase A) and MMP-9 (gelainase B) play an important role in cancer invasion because of their ability to degrade type IV collagen, a major component of basement membranes.